2008
DOI: 10.1002/jmri.21505
|View full text |Cite
|
Sign up to set email alerts
|

Free‐breathing, nongated real‐time delayed enhancement MRI of myocardial infarcts: A comparison with conventional delayed enhancement

Abstract: Purpose:To compare a free-breathing, nongated, and black-blood real-time delayed enhancement (RT-DE) sequence to the conventional inversion recovery gradient echo (IR-GRE) sequence for delayed enhancement MRI. Materials and Methods:Twenty-three patients with suspected myocardial infarct (MI) were examined using both the IR-GRE and RT-DE imaging sequences. The sensitivity and specificity of RT-DE for detecting MI, using IR-GRE as the gold standard, was determined. The contrast-to-noise ratios (CNR) between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Single‐shot sequences also do not provide any functional information. A real‐time delayed enhancement sequence (20) has been recently shown to provide viability and anatomical images (during free‐breathing and without cardiac gating) with improved contrast between infarct and blood (21); however, the temporal resolution of this method does not allow for the visualization of cardiac wall motion. MCLE imaging can be acquired at the same (or higher) resolution as IR‐GRE imaging with the same temporal resolution as cine SSFP acquisitions.…”
Section: Discussionmentioning
confidence: 99%
“…Single‐shot sequences also do not provide any functional information. A real‐time delayed enhancement sequence (20) has been recently shown to provide viability and anatomical images (during free‐breathing and without cardiac gating) with improved contrast between infarct and blood (21); however, the temporal resolution of this method does not allow for the visualization of cardiac wall motion. MCLE imaging can be acquired at the same (or higher) resolution as IR‐GRE imaging with the same temporal resolution as cine SSFP acquisitions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the presence of gadolin-ium can interfere with nulling of blood signal and should be administered after dark blood imaging. However, real-time nongated black blood sequences with gadolinium contrast administration have proven to be effective for evaluating myocardial ischemia [9].…”
Section: Dark Blood Imagingmentioning
confidence: 99%
“…However, the saturation-recover pulse consists of applying a 90° flip angle and is less subject to signal intensity variations than IR techniques. Smaller flip angles can be used to maintain spatial resolution [9]. The saturation-recover pulse is often used in combination with GRE and hybrid GRE-EPI pulse sequences for perfusion-weighted imaging and myocardial tagging.…”
Section: Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Another retrospective clinical study on 25 patients referred for implantable cardioverter defibrillator (ICD) therapy has revealed that peri‐infarct border zone measurement along with papillary muscle infarct assessment using 2D MCLE prior to ICD implantation might be more sensitive, compared to using 2D LGE, in predicting proper ICD therapy in patient with prior MI . To date, MCLE has demonstrated clear clinical benefits in a range of clinical studies to advance myocardial viability assessment , particularly delineation of the peri‐infarct border zone.…”
Section: Introductionmentioning
confidence: 99%